FLOUTING MAXIMS BY EFL TERTIARY STUDENTS IN EFL CLASSROOM INTERACTION - Prabawa, Wawa Puja (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2020)
This present study tries to elaborate the area of study particularly conversation principle on EFL area especially in Indonesia EFL context. This study focuses on the identifying different types of conversational implicatures especially flouting maxim found in EFL classroom interaction. Adopting a qualitative approach, it involved lecturer and students dialogue in classroom interaction through observation and video recording. The results show that students flouting maxim of quality and manner in classroom interaction. Students preferred not to tell the truth information and answer the yes-no question using long response answer and ambiguous words.